A Novel Approach for Arabic Text Steganography Based on the “BloodGroup” Text Hiding Method - Malalla, S.; Shareef, F. R. (Engineering, Technology & Applied Science Research, 2017)
Steganography is the science of hiding certain messages (data) in groups of irrelevant data possibly of other form. The purpose of steganography is covert communication to hide the existence of a message from an intermediary. Text Steganography is the process of embedding secret message (text) in another text (cover text) so that the existence of secret message cannot be detected by a third party. This paper presents a novel approach for text steganography using the Blood Group (BG) method based on the behavior of blood group. Experimentally it is found that the proposed method got good results in capacity, hiding capacity, time complexity, robustness, visibility, and similarity which shows its superiority as compared to most several existing methods.